2020
DOI: 10.1242/bio.048728
|View full text |Cite
|
Sign up to set email alerts
|

The absence of SOX2 in the anterior foregut alters the esophagus into trachea and bronchi in both epithelial and mesenchymal components

Abstract: In the anterior foregut (AFG) of mouse embryos, the transcription factor SOX2 is expressed in the epithelia of the esophagus and proximal branches of respiratory organs comprising the trachea and bronchi, whereas NKX2.1 is expressed only in the epithelia of respiratory organs. Previous studies using hypomorphic Sox2 alleles have indicated that reduced SOX2 expression causes the esophageal epithelium to display some respiratory organ characteristics. In the present study, we produced mouse embryos with AFG-spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Nkx2-1 and Sox2 are transcription factors required for the development of the tracheal and esophageal endoderm epithelia, respectively ( Minoo et al, 1999 ; Que et al, 2007 ). Nkx2-1 −/− mutants have a single undivided foregut tube of esophageal character, whereas deletion of Sox2 from the foregut results in an undivided foregut tube of tracheal character ( Kuwahara et al, 2020 ; Que et al, 2009 , 2007 ; Teramoto et al, 2020 ; Trisno et al, 2018 ). A re-analysis of these mutants showed that the single undivided foregut in both the Sox2 and Nkx2-1 mutant embryos was correctly patterned.…”
Section: Resultsmentioning
confidence: 99%
“…Nkx2-1 and Sox2 are transcription factors required for the development of the tracheal and esophageal endoderm epithelia, respectively ( Minoo et al, 1999 ; Que et al, 2007 ). Nkx2-1 −/− mutants have a single undivided foregut tube of esophageal character, whereas deletion of Sox2 from the foregut results in an undivided foregut tube of tracheal character ( Kuwahara et al, 2020 ; Que et al, 2009 , 2007 ; Teramoto et al, 2020 ; Trisno et al, 2018 ). A re-analysis of these mutants showed that the single undivided foregut in both the Sox2 and Nkx2-1 mutant embryos was correctly patterned.…”
Section: Resultsmentioning
confidence: 99%
“…The complementary distribution of Nkx2.1 and Sox2 determines the DV pattern of the foregut tube. [37][38][39] Nkx2.1, an essential TF for trachea and lung specification, 40 is initially expressed by E9.0, 24 specifically in the ventral area of the anterior foregut endoderm. In Nkx2.1 null mice, the trachea fails to appear, resulting in tracheal agenesis, 38 although bilateral bronchial tubes arise from the esophagus and connect to profoundly hypoplastic lungs.…”
Section: Lineage Specification With DV Patterning (E85-e105)mentioning
confidence: 99%
“…The complementary distribution of Nkx2.1 and Sox2 determines the DV pattern of the foregut tube. 37 , 38 , 39 …”
Section: Four Steps In Tracheal Developmentmentioning
confidence: 99%
“…Nkx2-1 and Sox2 are transcription factors required for development of the tracheal and esophageal endoderm epithelial, respectively (Minoo et al, 1999;Que et al, 2007). Nkx2-1 -/mutants have a single undivided foregut tube of esophageal character, whereas deletion of Sox2 from the foregut results in an undivided foregut tube of respiratory character (Kuwahara et al, 2020;Que et al, 2009;Que et al, 2007;Teramoto et al, 2020;Trisno et al, 2018). A reanalysis of these mutants showed that both the Sox2 and Nkx2-1-null embryos exhibited a downregulation of Foxf1 and upregulation of Sox9 in the ventral mesenchyme, although there were far fewer Sox9+ chondrocytes in the Nkx2-1 mutant compared to the Sox2 mutant or wildtype controls (Supplemental Figure 2A) (Que et al, 2009;Teramoto et al, 2020).…”
Section: Dynamic Foxf1 and Sox9 Localization During Tracheal Developmentmentioning
confidence: 99%
“…Nkx2-1 -/mutants have a single undivided foregut tube of esophageal character, whereas deletion of Sox2 from the foregut results in an undivided foregut tube of respiratory character (Kuwahara et al, 2020;Que et al, 2009;Que et al, 2007;Teramoto et al, 2020;Trisno et al, 2018). A reanalysis of these mutants showed that both the Sox2 and Nkx2-1-null embryos exhibited a downregulation of Foxf1 and upregulation of Sox9 in the ventral mesenchyme, although there were far fewer Sox9+ chondrocytes in the Nkx2-1 mutant compared to the Sox2 mutant or wildtype controls (Supplemental Figure 2A) (Que et al, 2009;Teramoto et al, 2020). Together, these data indicate that the emergence of tracheal chondrocytes with an upregulation of Sox9 and a downregulation of Foxf1 is influenced by the epithelial identity, but not dependent on tracheoesophageal separation.…”
Section: Dynamic Foxf1 and Sox9 Localization During Tracheal Developmentmentioning
confidence: 99%